Chemical Vapor Deposition of High‐Optical‐Quality Large‐Area Monolayer Janus Transition Metal Dichalcogenides. Issue 38 (21st August 2022) - Gan, Ziyang; Paradisanos, Ioannis; Estrada‐Real, Ana; Picker, Julian; Najafidehaghani, Emad; Davies, Francis; Neumann, Christof; Robert, Cedric; Wiecha, Peter; Watanabe, Kenji; Taniguchi, Takashi; Marie, Xavier; et al.
Abstract: One‐pot chemical vapor deposition (CVD) growth of large‐area Janus SeMoS monolayers is reported, with the asymmetric top (Se) and bottom (S) chalcogen atomic planes with respect to the central transition metal (Mo) atoms. The formation of these 2D semiconductor monolayers takes place upon the thermodynamic‐equilibrium‐driven exchange of the bottom Se atoms of the initially grown MoSe2 single crystals on gold foils with S atoms. The growth process is characterized by complementary experimental techniques including Raman and X‐ray photoelectron spectroscopy, transmission electron microscopy, and the growth mechanisms are rationalized by first principle calculations. The remarkably high optical quality of the synthesized Janus monolayers is demonstrated by optical and magneto‐optical measurements which reveal the strong exciton–phonon coupling and enable an exciton g ‐factor of −3.3. Abstract : Monolayers of Janus SeMoS with asymmetric top (Se) and bottom (S) chalcogen atomic planes with respect to the central transition metal (Mo) atoms are synthesized using a one‐pot chemical vapor deposition process and its high optical quality is demonstrated by low‐temperature magneto optical spectroscopy.